Analisis Bibliometrik Klasifikasi Biaya Dalam Konteks Produksi Serta Perannya Terhadap Optimalisasi Goals Perusahaan (Literature Riview) - Khaddafi, Muammar; Nurhayati, Nurhayati; Deviani, Yola; Ananda, Suci; Kurnianto, Nugra (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2024)
This article analyzes the impact of production costs and their classification on company objectives through a literature study using descriptive qualitative methods. Through a search on Google Scholar with the keywords